Structural and immunohistochemical analysis of the follicular atresia of Vanellus chilenis (Charadriidae) and Himantopus melanurus (Recurvirostridae) - Bulfon, Mirian (2009)
We studied the structural and immunohistochemical aspects of the follicular atresia and interpreted the process of cell death in the ovary of Vanellus chilenis and Himantopus melanurus. We used five female adults of each species at the stage of gonadal recrudescence. The gonads were removed, weighed, fixed and processed with the technique of inclusion in paraffin. The sections were stained with Hematoxylin - Eosin, Trichromic Mallory, Nuclear Reaction Feulgen. The technique TUNEL was employed for marking apoptotic cells. According to the morphohistologic characteristics of analyzed atretic follicles we identified two kinds of atresia in both bird species: a) Non-bursting atresia, where follicular walls remain intact, including lipid atresia of primordial oocytes and lipid glandular atresia of previtellogenic and small vitellogenic follicles and b) Bursting atresia, characterized by the breakdown of the follicular walls of vitellogenic follicles higher than of 500 µm. In the gonadal phase, we observed lipid and lipid-glandular follicles, while bursting follicles were scarce. Apoptosis was detected at the start of involution in the granulosa cells of the lipid glandular follicles by employing the nuclear reaction of Feulgen, and was corroborated with the TUNEL technique. However, a notorious necrosis marked the final stages of the different types of involutive follicles of the two species. Based on these results, we infer that cell death is a normal physiological mechanism in the remodeling of ovaries in V. chilenis and H. melanurus and that the pr